Topics in fiscal policy: Evidence from a representative survey of the German population - Bernd Hayo; Florian Neumeier; Matthias Uhl (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
This paper provides background information and basic descriptive statistics for a representative survey of the German population conducted on our behalf by GfK in the first quarter of 2013. The survey addresses important topics in fiscal policy, including: 1) public preferences on the composition of fiscal expenditure; 2) public preferences on public debt; 3) the effect of tax changes on consumption and savings; and 4) the effect of tax changes on labour market activities.
Keywords: E21; E62; H30; J22; 330; Survey evidence; Fiscal policy; Public debt; Public preferences; Consumption; Labour supply